Going Beyond the One-Shot: Spiraling Information Literacy Across Four Years - Egan, Shawna E.; Witt, Alan N.; Chartier, Shana M. (Internet reference services quarterly, 2017)
Many institutions overwhelm the first year seminar with "one-shot" library instruction sessions, which are not necessarily linked to any form of assignment or assessment. So how can librarians maintain information literacy instruction throughout a student's academic career? Data collected by the Rivier University librarians showcases the ability to implement information literacy more effectively by streamlining and leveling it out over a four-year period.